Ionic Conductivity of Chitosan-based Polymer Electrolyte with Polyethylene Glycol (PEG) as Plasticizer and KCl as Alkaline Ion Transport Source - Maddu, Akhiruddin; Kadapi, Muhamar; Sofian, Irmansyah (Program Studi Pendidikan Fisika UHAMKA, 2018)
Polymer electrolyte films were fabricated utilizing chitosan biopolymer plasticized with polyethylene glycol (PEG) and KCl addition as ionic transport source. The precursor solution was prepared by mixing the chitosan in acetic acid solution and PEG that act as a plasticizer. Into the mixed solution was added KCl salt for as alkalin ion transport source in the polymer electrolyte. The polymer electrolyte films were fabricated by the casting method onto the petri glass. The influence of KCl content on ionic conductivity of the composite polymer electrolyte film was studied. The ionic conductivity of the composite polymer electrolyte film was characterized using LCR meter at a frequency of 1 kHz. The best ionic conductivity was found for the film containing 45 wt% of KCl salt. The activation energy was determined by using Arrhenius plot based on conductivity data at varied temperature. It has been found that the activation energy of the composite polymer electrolyte films varied to the KCL content in the composite polymer electrolyte films. The highest activation energy was found for the polymer electrolyte film with 45 wt% of KCl content.